AUTOIMMUNE OPTIC NEUROPATHY (AON) PROFILE AT OPHTHALMOLOGY OUTPATIENT CLINIC OF A TERTIARY HOSPITAL IN SURABAYA, INDONESIA - Devanty Dwi Santosa; Lukisiari Agustini; Artaria Tjempakasari (Majalah Biomorfologi, 2024)
Highlights Autoimmune optic neuropathy (AON) is one of the diseases that involve the central nervous system (CNS) and can result in disability if not treated quickly and appropriately. The autoimmune optic neuropathy (AON) patient's profile, including disease etiology and therapy, is essential to minimize the incidence of AON.   Abstract Background: Autoimmune optic neuropathy (AON) is a kind of optic neuritis that causes progressive and severe vision loss. The presence of an autoimmune disease usually characterizes the diagnosis of this disease. Several autoimmune processes that can cause AON are Multiple Sclerosis (MS), Neuromyelitis Optica Spectrum Disorder (NMOSD), Myelin Oligodendrocyte Glycoprotein Immunoglobulin (MOG-IgG), and other disorders, specifically systemic autoimmune disease, such as Systemic Lupus Erythematous (SLE), Sjogren's Syndrome, and Sarcoidosis. Risk factors for AON involve young adults and women. Most of the patients received therapy according to the ONTT protocol and underwent outpatient treatment with oral methylprednisolone or prednisone. Objective: The study aimed to obtain the autoimmune optic neuropathy (AON) profile in patients at the Ophthalmology Outpatient Installation of Dr. Soetomo General Academic Hospital Surabaya, Indonesia, in the 2017-2022 Period. Material and Method: This retrospective descriptive study used medical records; 70 subjects were included. Result: Most subjects suffered from SLE (55.7%) as the cause of AON and received therapy according to the ONTT protocol, namely oral methylprednisolone or prednisone (67.1%) with outpatient therapy. Some patients were given other therapies (25.7%), such as mecobalamin and other B complex vitamins. Conclusion: AON is an uncommon condition. However, if not treated promptly and effectively, it can result in handicaps. This study may serve as a reference for future relevant research and as an attempt to prevent the disease.